Remuneration of public servants in the Federal Republic of Germany - Чанишева, Галія Інсафівна; Чанишева, Г. І.; Чанишева, Галия Инсафовна; Chanysheva, Haliia I.; Chanysheva, Galiya; Наливайко, Лариса Романівна; Наливайко, Л. Р.; Наливайко, Лариса Романовна; Nalyvaiko, Larysa R.; Козін, Сергій Миколайович; Козін, С. М.; Козин, Сергей Николаевич; et al. (Baltija Publishing, 2018)
The aim of the article is to determine the specificities of the remuneration of civil servants in the Federal Republic of Germany. The subject of the study is the remuneration of civil servants in the Federal Republic of Germany. Methodology. The study is based on the use of general scientific and special-scientific methods and techniques of scientific knowledge. The dialectical method enabled to interrogate the development of the institution of the remuneration of civil servants in the Federal Republic of Germany. The comparative legal method enabled to compare doctrinal approaches to this issue. The system-structural method enabled to determine the elements of the remuneration of civil servants of the Federal Republic of Germany. Methods of analysis and synthesis helped study certain parts of this institute to formulate further conclusions about its most optimal functioning. The logicsemantic method was used to determine the content of the principles of “ensuring a decent standard of living for a public servant,” “equality of public service actors” and “allowance/supplies”. The normative-dogmatic method enabled to analyse the content of legal regulations of the domestic legislation and the legislation of the Federal Republic of Germany on the issue. Practical implications. The determination of the specificities of the remuneration of public servants in the Federal Republic of Germany enabled to make recommendations for improving the remuneration system of this category of employees in Ukraine, as well as identify problematic issues that require further consideration and research. Relevance/originality. The author’s definition of the concept of “remuneration of public servants” is proposed and the specific features of this institute, insufficiently studied before, are analysed. The article analyses the specificities of the remuneration of public servants. Their list is determined and the content of each of them is disclosed. The specificities of the remuneration of public servants are substantiated in comparison with other categories of employees. The study of the positive experience of Germany enabled to suggest: to adopt a special legal regulation on the remuneration of public servants in Ukraine, that is, the Law of Ukraine “On Remuneration of Public Servants”; to provide in the norms of the Law of Ukraine “On Public Service” the allowances for the professionalism of a public servant; to provide public servants with the opportunity to carry out another paid activity subject to the special permission of the head of a state body.

Метою статті є визначення особливостей оплати праці державних службовців у ФРН. Предметом дослідження є оплата праці державних службовців у ФРН. Методологія. Дослідження ґрунтується на використанні загальнонаукових та спеціально-наукових методів і прийомів наукового пізнання. Діалектичний метод дозволив дослідити розвиток інституту оплати праці державних службовців у ФРН. Порівняльно-правовий метод дозволив порівняти доктринальні підходи до цього питання. Системно-структурний метод дозволив визначити елементи оплати праці державних службовців ФРН. Методи аналізу та синтезу допомогли дослідити окремі частини цього інституту, щоб сформулювати подальші висновки щодо його найбільш оптимального функціонування. Логіко-семантичним методом визначено зміст принципів «забезпечення гідного рівня життя державного службовця», «рівності суб’єктів державної служби» та «допомоги/забезпечення». Нормативно-догматичний метод дозволив проаналізувати зміст правових норм вітчизняного законодавства та законодавства Федеративної Республіки Німеччина з цього питання. Практичні наслідки. Визначення особливостей оплати праці державних службовців у ФРН дозволило сформулювати рекомендації щодо вдосконалення системи оплати праці цієї категорії працівників в Україні, а також визначити проблемні питання, що потребують подальшого розгляду та дослідження. Актуальність/оригінальність. Запропоновано авторське визначення поняття «оплата праці державних службовців» та проаналізовано недостатньо досліджені особливості цього інституту. У статті аналізуються особливості оплати праці державних службовців. Визначається їх перелік та розкривається зміст кожного з них. Обґрунтовано особливості оплати праці державних службовців у порівнянні з іншими категоріями працівників. Вивчення позитивного досвіду Німеччини дозволило запропонувати: прийняти спеціальне правове регулювання щодо оплати праці державних службовців в Україні, тобто Закон України «Про оплату праці державних службовців»; передбачити в нормах Закону України «Про державну службу» надбавки за професіоналізм державного службовця; надавати державним службовцям можливість здійснювати іншу оплачувану діяльність за наявності спеціального дозволу керівника державного органу.
Nalyvaiko L. Remuneration of public servants in the Federal Republic of Germany / L. Nalyvaiko, G. Chanysheva, S. Kozin // Baltic Journal of Economic Studies. - Vol. 4. - № 5. - Baltija Publishing, 2018. - Р. 228-232.
Keywords: remuneration; labour; public servant; Germany; labour legislation; оплата праці; праця; державний службовець; Німеччина; трудове законодавство; Research Subject Categories::LAW/JURISPRUDENCE